The Banality of Necessity: A Materialist Correction to Hannah Arendt's Ethics of Thinking: Banalitas Keniscayaan: Suatu Koreksi Materialis atas Etika Berpikir Hannah Arendt - Stefanus Galang Ardana (STF Driyarkara - Diskursus, 2026)
This article problematizes Hannah Arendt’s concept of thinking in The Life of the Mind, especially the tension between the activity of thinking as an internal dialogue (two-in-one) and the material conditions necessary for it. Based on the phenomenon of “thoughtlessness” (tuna pikir), this work contends that the lack of thinking in the precarious subject is not a moral failure, but a structural outcome of the political economy of time. With a materialist framework using Marx’s alienation and Jameson’s political unconscious, this article stages a phenomenological critique of three literary works: Ahmad Tohari’s Orang-Orang Proyek, Kazuo Ishiguro’s The Remains of the Day, and Franz Kafka’s The Trial. The analysis uncovers that the total consumption of the body (Tohari), the commodification of the self (Ishiguro), and the colonization of time (Kafka) are, by their nature, the reasons why the “withdrawal” Arendt needs for judgment is not possible. This article ends with the idea of the Banality of Necessity—a state in which the survival imperative closes down critical reflection—which constitutes a materialist correction to Arendt’s ethics. Abstrak Artikel ini mempersoalkan konsep “berpikir” (thinking) dalam filsafat Hannah Arendt, khususnya ketegangan antara aktivitas berpikir sebagai dialog batin (two-in-one) dengan kondisi material yang memungkinkannya. Berangkat dari fenomena tuna pikir, penelitian ini mengajukan tesis bahwa absennya aktivitas berpikir pada subjek prekariat bukanlah kegagalan moral, melainkan konsekuensi struktural dari ekonomi politik waktu. Dengan menggunakan kerangka materialis yang mengacu pada konsep alienasi Marx dan nirsadar politik Jameson, artikel ini melakukan kritik fenomenologis atas tiga karya sastra: Orang-Orang Proyek (Ahmad Tohari), The Remains of the Day (Kazuo Ishiguro), dan The Trial (Franz Kafka). Analisis menunjukkan bahwa konsumsi total atas tubuh (Tohari), komodifikasi diri (Ishiguro), dan kolonisasi waktu (Kafka) secara struktural menghalangi “penarikan diri” (withdrawal) yang disyaratkan Arendt. Artikel ini menyimpulkan dengan mengajukan konsep “Banalitas Keniscayaan” (The Banality of Necessity)—sebuah kondisi di mana imperatif bertahan hidup mematikan refleksi kritis—sebagai koreksi materialis terhadap etika Arendt. Kata-kata Kunci: Hannah Arendt, materialisme, tuna pikir, prekaritas, sastra